Improvements in Survival and Early Retirement Rates – Real-World Evidence on Danish Breast Cancer Patients 2004–2018 - Khan H; Rudolfsen JH; Olsen J; Borgquist S; Poulsen PB (Cancer Management and Research, 2023)
Humma Khan,1 Jan Håkon Rudolfsen,2 Jens Olsen,2 Signe Borgquist,3 Peter Bo Poulsen1 1Pfizer Denmark, Ballerup, Denmark; 2Incentive, Holte, Denmark; 3Department of Oncology, Aarhus University Hospital and Aarhus University, Aarhus, DenmarkCorrespondence: Peter Bo Poulsen, Pfizer Denmark, Lautrupvang 8, Ballerup, 2750, Denmark, Tel +45 2920 3211, Email PeterBo.Poulsen@pfizer.comBackground: Historically, Denmark has had poor survival for cancer patients relative to other western countries with comparable health-care systems. In this study, we examine the long-term cancer impact of a nationwide reform addressing all cancer diagnostics, implemented in 2006. The analyses include patients diagnosed with breast cancer and their spouses (informal caregivers). Patients and their spouses diagnosed before and after the reform were compared. Focus is on the potential impact on overall survival, early retirement, sick leave, unemployment as well as earnings (income).Methods: In a nationwide retrospective cohort study utilizing the Danish National Patient Register we identified 77,474 breast cancer patients between 1st January 2002 and 31st December 2018. Data was merged with the National Cancer Register, the Central Person Register, the Education Register, the DREAM Register and the Income Register using citizens’ personal identification number. Spouses of cancer patients were identified through the Central Person Register. Propensity score matching was applied to match populations before and after the reform. Analyses on matched as well as unmatched populations were performed.Results: In a matched sample, risk of mortality was reduced by 15% for breast cancer patients diagnosed after the reform. Moreover, there was a 15% reduced risk of early retirement. The patients diagnosed after the reform had reduced income three to five years after diagnosis relative to those diagnosed before the reform, likely due to survival bias and labor market conditions. In an unmatched sample of patients diagnosed two years before or after the reform, mortality was reduced by 7%.Conclusion: Implementation of the nationwide cancer reform together with advancement in new cancer treatments had a positive impact on survival and reduced risk of early retirement. The results from this study are reassuring that relevant health-care reforms improve cancer outcome.Keywords: breast cancer, survival, early retirement, register data